2023
DOI: 10.1002/adma.202211487
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Polyimide‐Organosilicate Hybrid Films for High‐Temperature Capacitive Energy Storage

Abstract: well drilling. [1][2][3] Nowadays, dielectric materials with excellent high-temperature capacitive properties are in great demand because of the heat inevitably generated by compact high-power electronic systems. [4][5][6][7] For example, the operating temperature of capacitors is 140-150 °C in green-energy vehicle inverters and reaches 200 °C in electrified aircraft. Biaxially oriented polypropylene (BOPP), the mainstream commercial polymer dielectrics, has discharged energy densities (U e ) <4.0 J cm −3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 63 publications
0
42
0
Order By: Relevance
“…[4][5][6][7][8] In practical applications, dielectric capacitors are always exposed to harsh environments, and their operating temperature always exceeds 140 1C. 9,10 However, the maximum operating temperatures of the current used commercial dielectric polymers are usually below 100 1C. 11,12 Therefore, it is critical to develop polymers with excellent reliability and stability at high-temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] In practical applications, dielectric capacitors are always exposed to harsh environments, and their operating temperature always exceeds 140 1C. 9,10 However, the maximum operating temperatures of the current used commercial dielectric polymers are usually below 100 1C. 11,12 Therefore, it is critical to develop polymers with excellent reliability and stability at high-temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer-based dielectric materials have high losses under high electric fields or high temperatures, and the losses will sharply increase with the applied temperature and electric field, which will lead to a decrease in U dis and efficiency. The commonly used biaxially oriented polypropylene film in commercial applications has a U dis of 2–3 J/cm 3 and can withstand operating temperatures of less than 85 °C. Polyetherimide (PEI) is a thermoplastic engineering resin with high glass transition temperature, excellent breakdown field strength, mechanical properties, and high temperature stability. Lin et al prepared high-entropy-induced ceramic nanofibers as a filler by electrospinning to enhance the energy storage performance of PEI. Due to the refined grain size, linear pyrochlore phase, and increased amorphous fraction of nanofillers, composites exhibit significantly enhanced U dis over the temperature range of 25–150 °C …”
Section: Introductionmentioning
confidence: 99%
“…Polyimide (PI) films are commonly used for external insulation of a spacecraft as they are resilient to the high applied voltage, thermally stable, lightweight, and versatile for a range of working conditions, such as the external layer of multilayer thermal blankets, insulating substrate of solar arrays, cable, and so on. Spacecraft operations are prone to anomalies due to the harsh space environment including ultra-high vacuum, high-energy beam, radiation, and thermal cycling. It is reported that more than half of the spacecraft anomalies (i.e., 54.2%) from the total 299 recorded cases were caused by the spacecraft charging and discharging effects, such as the net charge accumulation, induction of surface potential, and electrostatic discharges (ESD) caused by energetic particles. , These detrimental phenomena not only lead to the degradation of insulating materials but also perturb the telecommunication and electronic systems of the spacecraft, seriously threatening the reliability of the on-orbit spacecraft missions. Particularly, ESDs on the surface of the spacecraft, especially on solar arrays, has become one of the primary causes of on-orbit power system failures in spacecrafts. …”
Section: Introductionmentioning
confidence: 99%